СВЧ плазмохимическое осаждение структур для высокоапертурных планарных оптических волноводов - Grigorjantz, V. V.; Dolgov, A. P.; Kochmarev, L. Yu.; Shilov, I. P. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
The features of forming planar optical waveguides based on quartz glass in a waveguide-type microwave plasmatron operating in the H10 mode have been studied. The proposed microwave discharge excitation device has demonstrated its effectiveness in the development of optical structures of the composition SiO2–F|SiO2|SiO2–F. Based on the obtained optical waveguides, directional couplers with a 16×16 transfer matrix have been created, intended for use in fiber-optic systems for information transmission and processing.